A Visco-hypoplastic Constitutive Model for Rolled Asphalt - Gajári, György; Kisgyörgy, Lajos; Ádány, Sándor; Mahler, András; Lógó, János (Periodica Polytechnica Civil Engineering, 2021)
Experience has shown that the durability of “high-modulus” asphalts made with modified bitumen is unsatisfactory. The misdirected “development” forced in recent decades necessitates a more accurate understanding of the mechanical behavior of rolled asphalts, i.e., constitutive formulation of a numerical asphalt model. The authors elaborate a numerical procedure to model the visco-hypoplastic constitutive behavior of the rolled asphalts by the appropriate composition of the hypoplastic theory of soil mechanics and, taking into account the existing asphalt models. This proposal is justified because rolled asphalt is nothing more than an aggregate skeleton of mineral origin, the voids of which are filled with high-viscosity bitumen. The model allows to quantify the interaction of the two components, such as the formation of ruts due to pressure on the bitumen, the formation of cracks due to cooling-induced tensile stresses, and the viscous behavior of asphalt. Validity of this complex numerical model can already be considered proven theoretically, but it still needs to be experimentally verified for the viscous behavior. This new constitutive model has important theoretical and practical consequences such as a new visco-hypoplastic model of rolled asphalt as partially saturated granular material with cooling-induced isotropic residual stresses.